Ductile regime scratching of a rock sample in a laser assisted machining technique - (:unkn) unknown (American Society of Mechanical Engineers, 2017)
Rocks are playing an important role in the life of mankind since ancient times. One of the most significant characteristics of the rocks is their brittleness, which makes them exhibit a very poor machinability and usually severe fracture results during machining. In this paper, Micro-Laser Augmented Machining (μ-LAM) technique is applied on scratching a commercial rock, Gabbro-Labradorite, which is a composite of grained natural minerals such as feldspar, magnetite and mica. In the μ-LAM process, a laser is used to locally heat and thermally soften the materials below the scratching tool during the machining operation. In this paper, scratching tests have been done on the Gabbro-Labradorite minerals, with and without laser heating and results are compared and reported. Micro-laser assisted scratch tests (with an actual cutting tool) were successful in demonstrating the enhanced thermal softening of the feldspar and magnetite minerals. The effect of the laser power was studied by measuring the depths of the cuts for the scratch tests. When generating the scratches with a diamond tool, load range was increased from 50 to 500 mN. Laser powers of 10, 15, 20, and 25 Watt (W) have been utilized. All the tests were repeated two times to increase the reliability of the results. 3D profiles were generated by using a white light interferometer and microscopic images of the cuts have been reported. Results show that Ductile to Brittle Transition (DBT) depth, which is the critical depth for machining brittle materials, increased with the aid of the laser. Results are very important for the machining of the Gabbro-Labradorite to get a high material removal rate (MRR), low tool wear and better surface quality. ©2017 ASME.
Keywords: Ductile regime scratching; Gabbro-labradorite; Micro laser assisted machining